Sum Hope: Breaking The Numbers Barrier
The book for all those who think they \\\'can\\\'t do maths\\\'. It shows them they can. Do you have a mental block about numbers? Do you or your child find anything to do with figures impossibly difficult? Sum Hope is written for you- it\\\'s about people as well as maths. In this book you will discover that you know more maths than you think. You will be shown how to build on what you know and how to extend this into new skills and confidence with numbers. There is no unnecessary technical jargon: maths idwas are explained clearly, in human terms.